(untitled) - Sullivan, Jeremiah J. (Lexington, Mass, 1977)
Contents: introduction; the seabed issue; coastal zone juridictional issues; significant law of the sea positions taken; the noudle mining industry,...
Keywords: Ocean bottom (Maritime law),Đáy đại dương (luật Hàng hải)